Role of endothelial contracting and relaxing factors in the mechanism of endothelial dysfunction in subcutaneous arteries (microvasculature) of diabetic patients. - Rasool, Aida Hanum Ghulam (Pusat Pengajian Kesihatan, 2015)
This study aims to examine the signalling pathways underlying endothelium-dependent responses in subcutaneous arteries of humans with Type 2 diabetes mellitus (T2DM) by assessing the relative contributions of nitric oxide (NO), prostacyclin and endothelium derived hyperpolarising factor (EDH) to responses to endothelium-dependent and independent agonists. This study was approved by the Human Ethical Committee of Universiti Sains Malaysia (USM); work conducted in this study conformed to the provisions of the Declaration of Helsinki. Written informed consent was obtained from patients undergoing lower limb surgical procedures. Sixteen healthy controls and twenty diabetic patients between the ages of 18 to 65 years old were recruited among those undergoing lower limb surgical procedures. Acetylcholine hydrochloride, phenylephrine and sodium nitroprusside were purchased from Sigma Chemical Co. (St. Louis, MO). l-[(2- Chlorophenyl) diphenylmethyl]-1Hpyrazole (TRAM 34), 6,12,19,20,25,26-hexahydro-5,27:13,18:21,24-trietheno-l 1,7-metheno- 7H-dibenzo \b,n\ [l,5,12,16]tetraazacyclotricosine-5,13-diium dibromide (UCL 1684) and salbutamol were purchased from Tocris Bioscience (Bristol, UK). Indomethacin, L-NAME and prostacyclin were obtained from Cayman Chemical Company (Ann Arbor, MI). Distilled water was used to prepare the drug solutions, except for indomethacin, TRAM-34 and UCL 1684, which were dissolved in dimethyl sulphoxide (DMSO). Concentrations are given as final molar concentration in the bath solution. Primary antibodies against endothelial nitric oxide synthase (eNOS; AB5589), cyclooxygenase-1 (COX-1; AB53766), cyclooxygenase-2 (COX-2; AB15191), prostacyclin synthase (PGIS; AB23668), prostacyclin (IP; AB123419) receptor and horseradish peroxidase (HRP)-conjugated secondary antibodies (AB 6721) were purchased from Abeam (Cambridge, UK). A rabbit polyclonal antibody to 0-actin was purchased from Sigma Chemical Co. Subcutaneous tissues from lower limb surgical procedures were transported to Pharmacology Vascular laboratory in ice cold physiological salt solution. Subcutaneous arteries were dissected free of connective tissue and fat, and then cut into rings. Care was